2018
DOI: 10.1109/tmi.2018.2812151
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Influence of Spatial Constraints on Ultimate Receive Coil Performance for Monkey Brain MRI at 7 T

Abstract: The RF receive coil array has become increasingly vital in current MR imaging practice due to its extended spatial coverage, maintained high SNR, and improved capability of accelerating data acquisition. The performance of a coil array is intrinsically determined by the current patterns generated in coil elements as well as by the induced electromagnetic fields inside the object. Investigations of the ultimate performance constrained by a specific coil space, which defines all possible current patterns flowing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…An important property of the macaque coil is its improved ability to provide parallel imaging due to a higher loop density and shorter loop-to-subject distance [28]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…An important property of the macaque coil is its improved ability to provide parallel imaging due to a higher loop density and shorter loop-to-subject distance [28]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that theoretical performance limits could be used as absolute references against which to evaluate RF coil performance and to derive guidelines for optimal coil design 1,17–25 . For example, the ultimate intrinsic signal‐to‐noise ratio (UISNR) could be used to assess receive arrays, 26–29 while the associated ideal current patterns could be employed to guide coil design 30–33 . Ultimate performance bounds were also used to investigate transmit array performance, in terms of SAR and excitation homogeneity, as a function of the number of coil elements in RF shimming and parallel transmission 1,34 .…”
Section: Introductionmentioning
confidence: 99%
“…Gao et al 2018)-all coil were positioned at 1 cm above each model. Each coil was tuned, matched (<−15 dB) and excited with a 50 Ω port at 297.2 MHz which is the operating frequency of 7T proton MRI.EM field and SAR distributions were calculated by using the FIT (Finite Integration Technique) solver in the CST software and exported into MATLAB (Mathworks, Natick, Massachusetts, USA) for analysis.…”
mentioning
confidence: 99%